Perineal Massage during Second Stage of Labor to the Perineal Laceration Degree in Primigravida - Arafah, Sitti; Lotisna, David; Tiro, Eddy (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the effect of perineal massage during second stage of labor on the perineal laceration degree in primigravida. Methods: The design of this study was non randomized controlled trial by conducting massage training of the perineum to 20 obstetrics and gynecology residents. All residents had passed the normal delivery care training. Primigravida who met the inclusion criteria were included in this study. We assessed the degree of perineal laceration in this study. Data were analyzed using Chi square test in SPSS. Results: We obtained 103 subjects for massage group and 79 subjects for control group. There was a significant association between massage group and the incidence of intact perineum. In the massage group, most of perineal lacerations were first degree of laceration (52.4%); whereas, in the control group, most of them were second degree of laceration (77.2%). Statistical analysis showed a significant association between perineal massage and decreased of perineal laceration degree (p